The challenge of rangeland degradation in a temperate semiarid region of Argentina: the Caldenal - Fernandez, Osvaldo Alberto (2009)
The phytogeographical region known as the Caldenal comprises an area of approximately 10 million ha in the central temperate part of Argentina (35–40° S, 62–66° W). The original physiognomy of the vegetation consisted of a gramineous steppe with isolated shrubs and trees. Rangeland deterioration was initiated in the early-1900s with the introduction of livestock by the colonizing European ranchers. After a few decades of inappropriate use, the Caldenal proved to be a fragile environment. Major environmental impacts were: (a) The replacement of the most abundant palatable grasses Poa ligularis, Stipa clarazii, S. tenuis, Piptochaetium napostaense and Digitaria californica by low nutritive unpalatable grasses such as Stipa gynerioides, S. tenuissima, S. ambigua, S. bracychaeta and Elyonurus muticus; (b) The conversion of extensive areas dominated by grasses to a scrubland. There, frequent species are: Condalia microphylla, Lycium chilense, Prosopis alpataco, Larrea divaricata and Chuquiraga erinacea; (c) Depletion of plant cover resulting in incipient but increasing soil erosion in extensive areas. With the purpose of reversing this situation, the remit initiated 25 years ago was to develop management guidelines conducive to sustainable productivity while preserving the natural resources of the region. This work provides a comprehensive assessment of the impact of major stresses (drought, herbivory, fire) on grass and shrub responses, as well as more basic studies on the ecophysiology of these species. We have gained knowledge which is extremely useful to initiate rangeland utilization based on scientific information, facilitating increased sustainable rangeland productivity while preserving the natural resources.